Du développement durable à la transition : des démarches d’anticipation territoriales en recomposition - Rémi Le Fur (Temporalités)
Like sustainable development, proactive approaches are future-oriented. As concern for sustainable development escalates, local and regional authorities hae been undertaking increasingly proactive approaches. Public action has broadened the scope of the spatial and temporal issues it must answer, passing from local and short-term to global and long-term (end of the 21st century) issues. Though proactive approaches are on the receiving end of this evolution, they are also the vectors of change, since, thanks to adapting their practices, they contribute to improve the way sustainable development concerns are taken into account. Although proactive approaches are still open to improvement, with many questions still outstanding, it would appear that it is the stakeholders who must first be mobilized for the transition dynamics to work, but the latter must also remain flexible and adaptable.